Identifikasi Risiko Keselamatan dan Kesehatan Kerja Petugas Kebersihan di RSIA Bunda Ciputat - Akbari, Hadis (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2022)
Occupational safety and health are important aspects in controlling and reducing the risk of hazards arising from work activities in the hospital environment, including the cleaning staff. This study aims to identify the occupational safety and health risks of janitors at RSIA Bunda Ciputat. This research is descriptive with an observational approach using the Job Safety Analysis (JSA) method and interviews. The informants in this study were 9 janitors. Data were analyzed descriptively. The results of the identification of hazards include exposure to germs or disease viruses, needle sticks, exposure to hazardous and toxic substances, exposure to UV rays, scratches by sharp objects, and musculoskeletal disorders (pain in the waist, legs, and arms). With 28.1% the risk to the cleaning staff is at a high-risk level. 40.6% of the risk to the cleaning staff is at the moderate risk level and 31.3% has the low-risk category. The importance of management supervision and the commitment of officers in implementing occupational safety and health to create a healthy, safe and comfortable hospital environment for every worker.